UNDERGRADUATE CHEMSTRY EDUCATION STUDENTS’ ATTITUDE TOWARD USE OF COMPUTER AND INTERNET AND ITS INFLUENCE ON THEIR ACADEMIC ACHIEVEMENT IN KANO STATE. (UNIZIK Journal of STM Education, 2024)
This study investigated the influence of students’ attitudes towards the use of computer and internet resources on academic achievement among undergraduate chemistry students in Kano State. The study employed a correlational design, and a sample of 322 undergraduate chemistry students were selected using a proportionate stratified random sampling technique from four government-owned universities in Kano state, comprising 198 males and 124 females. The research instrument used was the Chemistry Undergraduates Attitude towards Computer and Internet Resources Questionnaire (CUATCIRQ). The reliability coefficients of the two sub-scales were 0.82 and 0.73 for items on utilization, and attitudes towards computer and internet resources, respectively, using Split Half method Cronbach Alpha was used to calculate the reliability index, for internal consistency. To measure academic achievement, students’ first semester examinations GPAs were used. Frequency count, means, standard deviation, ppmc and point-biserial correlation were used to answer the research questions, while Point bi-serial and Pearson product-moment correlation were used to test the null hypotheses at the 0.05 level of significance using SPSS version 25. The findings showed that Undergraduate chemistry students in Kano state university have a positive attitude toward use of computer and internet, and also gender varies with attitude in opposite directions. Furthermore there was no significant relationship between undergraduate chemistry students’ attitudes towards the use of computer and their academic achievement, as well as attitude towards internet resources and their academic achievement. Based on the study's findings, it is recommended that federal and state ministries of education should provide adequate provisions for computers, internet facilities, and overhead projectors, as well as a regular supply of electricity in schools. This will enhance attitudes towards the use of computer system and also internet resources and improve the academic achievement of undergraduate chemistry students.
Keywords: Attitude, Computer, Internet, Academic Achievement.